2023
DOI: 10.1126/science.abn1366
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic antibody receptor TRIM21 is required for effective tau immunotherapy in mouse models

Abstract: Aggregates of the protein tau are proposed to drive pathogenesis in neurodegenerative diseases. Tau can be targeted by using passively transferred antibodies (Abs), but the mechanisms of Ab protection are incompletely understood. In this work, we used a variety of cell and animal model systems and showed that the cytosolic Ab receptor and E3 ligase TRIM21 (T21) could play a role in Ab protection against tau pathology. Tau-Ab complexes were internalized to the cytosol of neurons, which enabled T21 engagement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Tripartite motif-containing protein 21 (TRIM21), a cytosolic IgG Fc receptor with ubiquitin ligase activity, plays a pivotal role in eliminating intracellular antigen/antibody (Ag/Ab) complexes 4 , a crucial mechanism underlying the innovative Trim-Away technology 30 . We hypothesized that TRIM21 might be instrumental in reducing the intraneuronal complexes formed by LCN with Aβ42 aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Tripartite motif-containing protein 21 (TRIM21), a cytosolic IgG Fc receptor with ubiquitin ligase activity, plays a pivotal role in eliminating intracellular antigen/antibody (Ag/Ab) complexes 4 , a crucial mechanism underlying the innovative Trim-Away technology 30 . We hypothesized that TRIM21 might be instrumental in reducing the intraneuronal complexes formed by LCN with Aβ42 aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that some TRIM proteins may participate in PQC (18)(19)(20)(21), although other TRIMs can aggravate protein aggregation (22). Moreover, TRIM21, a cytoplasmic antibody receptor, mediates the degradation of antibody-coated viruses or extracellular proteins that manage to enter the cytoplasm or intracellular proteins for which specific antibodies can be delivered (23)(24)(25)(26)(27). Here, we examined the role of the TRIM system in the pathogenesis of tauopathy, investigated its mechanism of action, and explored its utility for disease treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Like TRIM21, HOIP is broadly expressed in most cell types. Its Passive antibody therapy against misfolded protein tau is, like certain viral infections, susceptible to neutralisation by TRIM21 (Mukadam et al, 2023). This raises the question of whether linear ubiquitination would also be involved in the degradation of other substrates, in particular misfolded tau.…”
Section: Discussionmentioning
confidence: 99%
“…While initially discovered as a mechanism against non-enveloped viruses such as adenovirus, it has been demonstrated that this pathway can also degrade pathological protein aggregates such as tau fibrils during immunotherapy against neurodegenerative disorders (McEwan et al ., 2017; Mukadam et al ., 2023). This broad substrate specificity has been exploited in the development of an experimental technique called Trim-Away to deplete cytosolically accessible proteins as a knock-down tool (Clift et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%